Advances and prospects of transcription‐factor‐based biosensors in high‐throughput screening for cell factories construction. Issue 2 (4th July 2022) - Li, Changfan; Wang, Chang; Zhu, Jiang; Xue, Feng; Sun, Xiaoman; Gu, Yang
Abstract: Non/semi‐rational engineering strategies can improve the performance of microbial cell factories under the situations of indistinct metabolic regulations and interactions. However, generating positive variants through these strategies is remarkably low. Using traditional screening methods to evaluate the performance of mutants, such as mass spectrometry and chromatography, is low‐throughput, slow‐detection, and labor‐intensive. Specifically, the efficiency of high‐throughput screening (HTS) for strain screening could reach even more 10 3 −10 6 strains/day, bridging the gap between non/semi‐rational engineering strategies and microbial cell factories construction. This review highlights transcription factor (TFs)‐based biosensors in the advances in developing synthetic biosensors for HTS. We hope that this review will help take full advantage of valuable TFs to guide the HTS technology and promote its development. Abstract : Transcription factors (TFs) have been successfully used for high‐throughput screening (HTS) of high‐yielding strains, avoiding tedious and time‐consuming detection. This review highlights the advances in developing synthetic biosensors for HTS, focusing on TFs‐based biosensors.